Pemahaman tentang Tuberkel Montgomery pada Ibu Hamil dan Menyusui di RT 03 Desa Mekarjaya Kabupaten Muaro Jambi - Hesty Hesty; Nurfitriani Nurfitriani (Prosiding Seminar Kesehatan Nasional, 2022)
Pregnancy will change many things in the body, including the breasts. In addition to getting bigger, the nipples may become more sensitive than usual. Other changes are related to the glands around the breast area, specifically in the areola. This change is the appearance of lumps in the breasts during pregnancy and breastfeeding. This condition, known as Montgomery's tubercles, is considered normal. The problem encountered in pregnant and lactating women is the lack of understanding of the lumps that appear in the area, so the purpose of this activity is to provide understanding and increase knowledge about Montgomery tubercles in RT 03 Mekarjaya Village, Muaro Jambi Regency. In the form of counseling with a time of approximately 40 minutes and preceded by a pre test and ending with a post test, using a questionnaire. This activity was carried out in October 2021. The community service method used a survey approach, lectures, discussions and sharing experiences on matters related to the problem of the appearance of lumps in the areola of the mammary. The results obtained are that mothers understand about the Montgomery glands and do not need to worry about it. If there are no signs and symptoms that point to breast cancer then there is no need to worry. The next activity needs to optimize how to care for the breasts themselves for pregnant and lactating women. This activity will of course be included in the Abdimas Health Journal as an output.